Does experience affect the cancer detection rate in cognitive fusion prostate biopsy? A comparison of the first and last 60 cases - ÇAM, HAYDAR KAMİL (My University, 2022)
Objective: We aimed to determine the contribution of the clinical experience gained in cognitive fusion prostate biopsy with the increase in the number of cases to the cancer detection rate. Materials and Methods: The records of 120 patients who underwent cognitive fusion biopsy were retrospectively analyzed. All patients underwent 3-T multiparametric magnetic resonance imaging (Mp-MRI) and they were evaluated with Prostate Imaging Reporting and Data System (PIRADS). The initial 60 cases were included in group 1, and the later subsequent 60 cases performed by the same surgeon were included in group 2. Any cancer and clinically significant prostate cancer (CSPrCa) detection rates in groups 1 and 2 were compared. Results: The mean ages of the patients for group 1 and group 2 were determined as 64.08 ± 8.15 and 65.15 ± 6.93 years, respectively. Age, prostate specific antigen (PSA), prostate volumes and the number of suspicious lesions of the groups were similar. Any cancer positivity rate was 33.3% for group 1, and 40% for group 2, without any significant intergroup difference (p=0.494). CSPrCa positivity was 40% and 70.83% for groups 1 and 2, respectively, and there was a significant improvement in CSPrCa detection in favor of group 2 (p=0.027). Conclusion: Regarding the cognitive fusion biopsies, a learning curve is required. It was concluded that the rate of detecting clinically significant prostate cancer was almost doubled with the increased experience in fusion biopsy.

Amaç: Bilişsel füzyon prostat biyopsisinde elde edilen klinik deneyimin vaka sayısındaki artışla birlikte kanser tespit oranına katkısını belirlemeyi amaçladık. Gereç ve Yöntemler: Kognitif füzyon biyopsisi yapılan 120 hastanın kayıtları geriye dönük olarak incelendi. Tüm hastalara 3-T multiparametrik manyetik rezonans görüntüleme (Mp-MRG) yapıldı ve Prostat Görüntüleme Raporlama ve Veri Sistemi (PIRADS) ile değerlendirildi. İlk 60 vaka grup 1'e dahil edildi ve daha sonra aynı cerrah tarafından gerçekleştirilen sonraki 60 vaka grup 2'ye dahil edildi. Herhangi bir kanser ve klinik olarak anlamlı prostat kanseri (CSPrCa) tespit oranları grup 1 ve 2'de karşılaştırıldı. Bulgular: Grup 1 ve grup 2 hastaların yaş ortalamaları sırasıyla 64.08 ± 8.15 ve 65.15 ± 6.93 yıl olarak belirlendi. Grupların yaş, prostat spesifik antijen (PSA), prostat hacimleri ve şüpheli lezyon sayıları benzerdi. Herhangi bir kanser pozitifliği oranı grup 1 için %33.3 ve grup 2 için %40 idi ve gruplar arası anlamlı bir fark yoktu (p=0.494). Grup 1 ve 2 için CSPrCa pozitifliği sırasıyla %40 ve %70.83 idi ve CSPrCa tespitinde grup 2 lehine anlamlı bir gelişme vardı (p=0.027). Sonuç: Bilişsel füzyon biyopsileri ile ilgili olarak bir öğrenme eğrisi gereklidir. Füzyon biyopsisinde artan deneyim ile klinik olarak anlamlı prostat kanseri tespit oranının neredeyse iki katına çıktığı sonucuna varıldı.
Keywords: Biyopsi; Kognitif Füzyon; Öğrenme Eğrisi; Manyetik Rezonans Görüntüleme; Prostat Kanseri; Biopsy; Cognitive Fusion; Learning Curve; Magnetic Resonance İmaging; Prostate Cancer